Selective etching of diamond single crystals obtained by thermal–gradient method - Супрун, Елена Михайловна; Ивахненко, Сергей Алексеевич (Eastern-European Journal of Enterprise Technologies, 2015)
Diamond single crystals were investigated using the selective etching. The crystals obtained by the thermal–gradient method using the Toroid type high– pressure device in the thermodynamic stability region at a pressure of 5.7 – 6.1 GPa and a temperature of 1420 – 1450°C were examined. Diamond samples had a cubooctahedral habit with the size of 2 – 4 mm; the crystal weight of 0,1 – 0,26 ct. Studies were carried out on plates prepared by parallel plane grinding (100). Before etching, diamond crystals were purified with a mixture of hydrochloric and nitric acids, then washed with chromic mixture. Etching was carried out using potassium nitride and potassium hydroxide at atmospheric pressure and a temperature of 550 ÷. 580°C in a platinum crucible. Experiments were performed in five stages, the total etching time – 85 min. A decrease in weight and changes in the etching patterns of diamond single crystals was observed. It was shown that diamond single crystals have a high perfection degree and low etchability at these temperatures.